Tannic acid modified lignin phenolic resin antibacterial adhesive and preparation method thereof

Through nanogenic treatment of alkali wood and introduce tannin acid/iron layer to prepare a antibacterial adhesive, it solves the problem of traditional phenolic resin adhesive dependence on fossil raw materials and prone to breeding fungi. Production of efficient and environmentally friendly adhesives.

CN119351013AActive Publication Date: 2025-01-24QILU UNIVERSITY OF TECHNOLOGY (SHANDONG ACADEMY OF SCIENCES)

Patent Information

Application Number
CN202411693542.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-24
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

Traditional phenolic resin adhesives rely on fossil raw materials, have high production costs, and are prone to bacteria and mold growth in humid environments, affecting their service life.

Method used

The lignin phenolic resin antibacterial adhesives modified by tannin acid are nanogenicized by the quality of alkali wood, and the tannin acid/iron layer is introduced to replace part of the phenol to improve the response activity and antibacterial effect.

Benefits of technology

It achieves a high proportion of phenol replacement, reduces production costs and environmental pollution, gives the adhesive a good photothermal antibacterial effect, and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119351013A_ABST
    Figure CN119351013A_ABST
Patent Text Reader

Abstract

The invention discloses a tannic acid modified lignin phenolic resin antibacterial adhesive and a preparation method thereof, and belongs to the technical field of bio-based adhesives. Alkali lignin is used as a raw material to prepare lignin nano-particles, then ferric trichloride and tannic acid are used for modifying the lignin nano-particles, and the tannic acid modified lignin phenolic resin antibacterial adhesive is prepared. Gallotannic acid / iron complexed lignin nano-particles are obtained, the gallotannic acid / iron complexed lignin nano-particles, phenol, formaldehyde and alkali liquor are mixed, and the lignin phenolic resin adhesive is prepared through an addition condensation reaction. The lignin phenolic resin adhesive prepared by the invention can realize high-proportion phenol substitution, has a good photo-thermal antibacterial effect, and provides a new way for development of an antibacterial environment-friendly adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of bio-based adhesives, and in particular relates to a tannic acid-modified lignin phenolic resin antibacterial adhesive and a preparation method thereof. Background Art

[0002] Phenolic resin adhesive is a polymer adhesive formed by the reaction of phenol and its derivatives (such as xylenol, resorcinol, etc.) and formaldehyde as the main raw materials under the action of a catalyst. The cured product has the characteristics of excellent heat resistance, high bonding strength, good aging resistance and excellent electrical insulation, and is widely used in the fields of plywood, artificial board and high-grade wood products. However, the preparation of phenolic resin is heavily dependent on fossil raw materials, with high production costs, and at the same time causes resource consumption and environmental pollution. In addition, traditional phenolic resin adhesives are restricted by their own molecular structure. When used in a humid environment and for a long time, they often cause the growth of bacteria, molds and other fungi, which seriously affects the actual efficacy and service life of the adhesive, and ultimately leads to the delamination of the bonding carrier.

[0003] Lignin is the most abundant aromatic compound in nature, with an annual output of up to 50 million tons. Lignin molecules contain a large number of phenol structures, making them an ideal biomass raw material for replacing phenol in the production of phenolic resins. However, due to the complex molecular structure, high heterogeneity, and few active sites of lignin, its reaction activity is low and it is difficult to be fully utilized. In order to improve the reaction activity of lignin, hydroxymethylation, amination, oxidation and other strategies are usually used to modify lignin. However, these modification strategies involve complicated reaction steps and require the consumption of a large amount of chemical reagents, which can easily cause serious environmental pollution.

[0004] Therefore, there is an urgent need to develop a low-cost adhesive with antibacterial properties. Summary of the invention

[0005] In order to solve the above technical problems, the present invention proposes a tannic acid modified lignin phenolic resin antibacterial adhesive and a preparation method thereof. The lignin nanoparticles prepared by the method of the present invention have a high specific surface area, which can fully expose the active sites of alkali lignin. The tannic acid / iron complex layer can further enrich the reaction sites of alkali lignin and achieve a high proportion of phenol replacement. At the same time, the tannic acid / iron complex layer can give the adhesive a good photothermal antibacterial effect.

[0006] To achieve the above object, the present invention provides the following technical solutions: One of the technical solutions of the present invention:

[0007] A method for preparing a tannic acid-modified lignin phenolic resin antibacterial adhesive comprises the following steps: using alkaline lignin as a raw material, obtaining lignin nanoparticles through dialysis; modifying the lignin nanoparticles with tannic acid and ferric chloride to obtain tannic acid / iron-complexed lignin nanoparticles; mixing the tannic acid / iron-complexed lignin nanoparticles with phenol, formaldehyde and alkaline solution, and preparing the tannic acid-modified lignin phenolic resin antibacterial adhesive through an addition condensation reaction.

[0008] Furthermore, the preparation method of the tannic acid modified lignin phenolic resin antibacterial adhesive comprises the following steps:

[0009] dissolving alkali lignin in an organic solvent, adding water and stirring to obtain a solution, dialyzing and freeze-drying the solution to obtain lignin nanoparticles;

[0010] The lignin nanoparticles are dispersed in water, ferric chloride and tannic acid are added, and after the reaction is completed, the lignin nanoparticles are centrifuged and freeze-dried to obtain tannic acid / iron complexed lignin nanoparticles;

[0011] The tannic acid / iron-complexed lignin nanoparticles, phenol, part of the formaldehyde solution and part of the alkali solution are mixed, and reacted at 65-75° C. for 30-60 minutes; then part of the formaldehyde solution and part of the alkali solution are added, and heated at 75-85° C. for 30 minutes; then the remaining formaldehyde solution and the remaining alkali solution are added, the temperature is raised to 85-95° C., and the temperature is kept for 60-90 minutes. After the phenolic resin reaches the required viscosity, the material is cooled and discharged to obtain the tannic acid-modified lignin phenolic resin antibacterial adhesive.

[0012] The present invention performs nano-processing on alkali lignin, which can effectively reduce its heterogeneity and increase the specific surface area, expose more active sites, and effectively improve the reaction activity of alkali lignin. In order to improve the antibacterial effect of the adhesive, an antibacterial agent is introduced during its preparation process. Tannic acid is a polyphenol compound derived from natural plants, which has the properties of antioxidant, free radical capture and antibacterial. The complex formed by it and metal ions has excellent near-infrared photothermal conversion ability. Under the irradiation of near-infrared light, these tannic acid-metal complexes can efficiently convert light energy into heat energy, produce a local high temperature effect, destroy the integrity of the bacterial cell membrane, and thus lead to the death of bacteria. In summary, the present invention uses low-cost and renewable alkali lignin as raw material, performs nano-processing, and further introduces tannic acid / iron complex to replace part of phenol to prepare phenolic resin adhesive, which has many unique advantages: on the one hand, nano-processing and introduction of tannic acid can effectively increase the reaction active sites of lignin and achieve a high proportion of phenol replacement; on the other hand, tannic acid / iron complex has good near-infrared photothermal conversion ability, which can give the adhesive photothermal antibacterial effect, which is of great significance for promoting the resource utilization of lignin and expanding the application scope of phenolic resin adhesive.

[0013] The organic solvent is one of tetrahydrofuran, methanol and acetonitrile; and / or

[0014] The volume ratio of the organic solvent to water is 1:(1-9).

[0015] The mass ratio of the lignin nanoparticles, ferric chloride and tannic acid is (10-20):(1-2):(2-4). The mass ratio of the lignin nanoparticles, ferric chloride and tannic acid will affect the loading amount and stability of the lignin nanoparticles on the tannic acid / iron complex, and further affect the antibacterial effect of the adhesive.

[0016] The mass of the tannic acid / iron complexed lignin nanoparticles is 30% to 70% of the mass of phenol.

[0017] The total amount of formaldehyde solution added is 80% to 100% of the total mass of phenol and tannic acid / iron complexed lignin nanoparticles, and the mass ratio of the formaldehyde solution added successively is 1:1:2. The synthesis of phenolic resin is a polycondensation reaction process, and formaldehyde and phenol are gradually polymerized under the action of a catalyst. Adding formaldehyde in batches can make the reaction more stable and avoid violent reactions caused by excessive formaldehyde, which is beneficial to control the temperature and rate of the reaction. In addition, adding formaldehyde in batches can also make the reaction more uniform and avoid uneven product performance caused by excessive local reactions.

[0018] The formaldehyde solution has a mass concentration of 35% to 40%, preferably a mass concentration of 37%.

[0019] The total amount of alkali solution added is 30% to 50% of the total mass of the lignin nanoparticles complexed with phenol and tannic acid / iron, and the mass ratio of the alkali solution added successively is 1:2:2; the alkali solution, as a catalyst, can accelerate the synthesis reaction of the phenolic resin. Adding the alkali solution in batches can gradually increase the reaction rate, avoiding the excessive reaction rate and temperature runaway caused by excessive alkali solution; in the synthesis process of the phenolic resin, there may be a variety of side reactions, and adding the alkali solution in batches can make the reaction more inclined to generate the desired phenolic resin and reduce the generation of by-products; adding the alkali solution in batches can also improve the stability of the product. In the reaction process, if the alkali solution is excessive, the structure of the resin may be unstable and easily decomposed or volatilized at high temperature, while adding it in batches can gradually increase the pH value in the reaction system, which is conducive to the stability of the resin structure.

[0020] The mass concentration of the alkali solution is 40%.

[0021] The alkali solution is one of a sodium hydroxide solution, a potassium hydroxide solution and a barium hydroxide solution.

[0022] The required viscosity is determined according to actual needs. For example, the required viscosity refers to a viscosity of 60 to 200 mPa·s.

[0023] The second technical solution of the present invention:

[0024] The present invention also provides a tannic acid-modified lignin phenolic resin antibacterial adhesive prepared according to the above preparation method.

[0025] The third technical solution of the present invention:

[0026] The present invention also provides application of the tannic acid-modified lignin phenolic resin antibacterial adhesive in the preparation of plywood.

[0027] The tannic acid modified lignin phenolic resin antibacterial adhesive of the present invention is widely used in the wood processing industry due to its good bonding performance, especially in the production of artificial boards. The use of tannic acid modified lignin modified phenolic resin can save the use of phenol, reduce the formaldehyde release, and achieve the purpose of environmental protection. Alkali lignin, as a natural renewable resource, contains active groups such as hydroxyl, methoxyl, and carboxyl in its chemical structure, is easy to functionally modify, and is an ideal raw material for synthesizing environmentally friendly wood adhesives. The development of tannic acid modified lignin phenolic resin antibacterial adhesive not only reduces dependence on fossil resources, but also reduces environmental pollution. The introduction of alkali lignin can improve the properties of the adhesive, such as increasing the bonding strength and reducing the curing time. Alkali lignin can replace phenol in part of the phenolic resin adhesive without affecting the performance of the board. Since alkali lignin is a low-priced raw material, its application in adhesives helps to reduce production costs. Tannic acid modified lignin phenolic resin antibacterial adhesive can reduce the residual amount of formaldehyde during the preparation process, thereby reducing formaldehyde release and improving the safety of the product. The tannic acid-modified lignin phenolic resin antibacterial adhesive of the present invention can be applied to the wood industry to prepare high-end artificial synthetic boards. At the same time, the cured phenolic resin is also a good carbon source and can be used to prepare energy storage electrode materials on supercapacitors. The tannic acid-modified lignin phenolic resin antibacterial adhesive of the present invention can also be used in other industrial fields, such as friction materials, foundry industry, etc., and is valued for its high temperature resistance and bonding strength. Exemplarily, the tannic acid-modified lignin phenolic resin antibacterial adhesive of the present invention can be used to bond wood, for example, the tannic acid-modified lignin phenolic resin antibacterial adhesive of the present invention can be used to bond wooden floors, cabinet boards, particle boards, etc.

[0028] Compared with the prior art, the present invention has the following advantages and technical effects:

[0029] (1) The present invention performs nano-processing on alkali lignin, which can fully expose the active sites of alkali lignin and significantly enhance its reaction activity. The tannic acid / iron complex layer can further enrich the active sites of alkali lignin, achieve a high proportion of phenol substitution, and the reaction process is simple.

[0030] (2) The tannic acid / iron complex layer has good near-infrared photothermal conversion ability, which can give the adhesive a photothermal antibacterial effect. Without the need to introduce additional antibacterial agents, the tannic acid-modified lignin phenolic resin antibacterial adhesive can have a good antibacterial effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] The accompanying drawings constituting a part of the present invention are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the accompanying drawings:

[0032] Figure 1 is a scanning electron microscope image of the lignin nanoparticles prepared in Example 1;

[0033] Figure 2 This is a scanning electron microscope image of the tannic acid / iron complexed lignin nanoparticles prepared in Example 1. DETAILED DESCRIPTION

[0034] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0035] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0036] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0037] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0038] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0039] Unless otherwise specified, the room temperature in the present invention is 25±2°C.

[0040] All raw materials used in the examples of the present invention are commercially available.

[0041] It should be pointed out that the matters not described in detail in the present invention are all conventional operating means in the art and are not the focus of the present invention. For example, specific methods such as dialysis and freeze-drying are all completed using conventional methods.

[0042] The present invention uses alkali lignin as a raw material to prepare lignin nanoparticles, and then uses ferric chloride and tannic acid to modify the lignin nanoparticles to obtain tannic acid / iron complexed lignin nanoparticles, and mixes the tannic acid / iron complexed lignin nanoparticles, phenol, formaldehyde and alkali solution to prepare a lignin phenolic resin adhesive through an addition condensation reaction. The lignin phenolic resin adhesive prepared by the present invention can achieve a high proportion of phenol replacement, and has a good photothermal antibacterial effect, providing a new way for the development of antibacterial and environmentally friendly adhesives.

[0043] The term "alkali lignin" is made by spray drying the waste liquid of alkali pulping through the latest production process. It is an industrial by-product, so it is also referred to as "industrial alkali lignin" in the following text. Alkali lignin is a brown (yellow) brown powder with a special smell. It can be dissolved in alkaline solutions and some organic solvents. Alkali lignin can be purchased directly or prepared according to literature. In the embodiments of the present invention, alkali lignin was purchased from Huatai Group Co., Ltd.

[0044] The technical solution of the present invention is further illustrated by the following embodiments.

[0045] Example 1

[0046] In the first step, 20 g of industrial alkali lignin was dissolved in 20 mL of tetrahydrofuran, and 180 mL of deionized water was added and stirred for 30 min. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain lignin nanoparticles. The scanning electron microscope image is shown in Figure 1 , it can be seen that the lignin nanoparticles prepared in this step are spherical and have a high specific surface area;

[0047] In the second step, 20 g of lignin nanoparticles were dispersed in deionized water, 1 g of ferric chloride and 2 g of tannic acid were added and stirred for 20 min, and tannic acid / iron complexed lignin nanoparticles were obtained by centrifugation and freeze drying. The scanning electron micrograph of the lignin nanoparticles is shown in FIG. Figure 2 It can be seen that the surface of the tannic acid / iron complexed lignin nanoparticles prepared in this step becomes rough and has particles attached, indicating that the tannic acid / iron complex is formed and attached to the surface of the lignin nanoparticles;

[0048] The third step is to take 6g of tannic acid / iron-complexed lignin nanoparticles, 20g of phenol, 5.2g of 37wt.% formaldehyde solution, and 1.6g of sodium hydroxide solution (concentration 40wt.%) into a reaction container and react at 65°C for 30min; then add 5.2g of 37wt.% formaldehyde solution and 3.2g of potassium hydroxide solution, and heat at 75°C for 30min; then add 10.4g of 37wt.% formaldehyde solution and 3.2g of sodium hydroxide solution, raise the temperature to 85°C, keep warm for 60min, cool and discharge, and obtain a lignin phenolic resin antibacterial adhesive modified with wood tannic acid.

[0049] According to the provisions of Section 4.17 of GB / T 17657-2013 "Test methods for physical and chemical properties of wood-based panels and veneer wood-based panels", poplar veneers were selected to prepare three-layer plywood and the strength of the plywood was tested. 2 The plywood prepared under the conditions of hot pressing temperature of 190℃, hot pressing pressure of 2.0MPa and hot pressing time of 10 minutes has a bonding strength of 1.5MPa measured according to the Class I plywood measurement method, which is greater than the national standard of 0.7MPa.

[0050] Example 2

[0051] In the first step, 20 g of industrial alkali lignin was dissolved in 20 mL of acetonitrile, and 140 mL of deionized water was added and stirred for 30 min. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain lignin nanoparticles;

[0052] In the second step, 20 g of lignin nanoparticles were dispersed in deionized water, 1 g of ferric chloride and 3 g of tannic acid were added and stirred for 20 min, and tannic acid / iron complexed lignin nanoparticles were obtained by centrifugation and freeze drying;

[0053] The third step is to take 8g of tannic acid / iron-complexed lignin nanoparticles, 20g of phenol, 6.3g of 40wt.% formaldehyde solution, and 2.2g of sodium hydroxide solution (concentration 40wt.%, the same below) into a reaction container and react at 70°C for 40min; then add 6.3g of 40wt.% formaldehyde solution and 4.4g of sodium hydroxide solution, and heat at 80°C for 40min; then add 12.6g of 40wt.% formaldehyde solution and 4.4g of sodium hydroxide solution, raise the temperature to 90°C, keep warm for 70min, cool and discharge, and obtain a tannic acid-modified lignin phenolic resin antibacterial adhesive.

[0054] The bonding strength of the adhesive prepared in this embodiment was tested using the same testing method as in Embodiment 1, and the bonding strength was found to be 1.4 MPa.

[0055] Example 3

[0056] In the first step, 20 g of industrial alkali lignin was dissolved in 20 mL of methanol, 100 mL of deionized water was added and stirred for 30 min. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain lignin nanoparticles;

[0057] In the second step, 20 g of lignin nanoparticles were dispersed in deionized water, 1 g of ferric chloride and 4 g of tannic acid were added and stirred for 30 min, and tannic acid / iron complexed lignin nanoparticles were obtained by centrifugation and freeze drying;

[0058] The third step is to take 10g of tannic acid / iron-complexed lignin nanoparticles, 20g of phenol, 7.5g of 35wt.% formaldehyde solution, and 3g of sodium hydroxide solution (concentration 40wt.%, the same below) into a reaction container and react at 75°C for 50min; then add 7.5g of 35wt.% formaldehyde solution and 3g of sodium hydroxide solution, and heat at 85°C for 50min; then add 15g of 35wt.% formaldehyde solution and 3g of sodium hydroxide solution, raise the temperature to 95°C, keep warm for 80min, cool and discharge, and obtain a tannic acid-modified lignin phenolic resin antibacterial adhesive.

[0059] The bonding strength of the adhesive prepared in this embodiment was tested using the same testing method as in Embodiment 1, and the bonding strength was found to be 1.4 MPa.

[0060] Example 4

[0061] In the first step, 20 g of industrial alkali lignin was dissolved in 20 mL of methanol, and 60 mL of deionized water was added and stirred for 30 min. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain lignin nanoparticles;

[0062] In the second step, 15 g of lignin nanoparticles were dispersed in deionized water, 2 g of ferric chloride and 4 g of tannic acid were added and stirred for 40 min, and tannic acid / iron complexed lignin nanoparticles were obtained by centrifugation and freeze drying;

[0063] The third step is to take 12g of tannic acid / iron-complexed lignin nanoparticles, 20g of phenol, 8g of 37wt.% formaldehyde solution, and 3.2g of potassium hydroxide solution (concentration 40wt.%, the same below) into a reaction container and react at 75°C for 60min; then add 8g of 37wt.% formaldehyde solution and 3.2g of potassium hydroxide solution, and heat at 85°C for 60min; then add 16g of 37wt.% formaldehyde solution and 6.4g of potassium hydroxide solution, raise the temperature to 95°C, keep warm for 90min, cool and discharge, and obtain a tannic acid-modified lignin phenolic resin antibacterial adhesive.

[0064] The bonding strength of the adhesive prepared in this example was tested using the same testing method as in Example 1, and the bonding strength was found to be 1.6 MPa.

[0065] Example 5

[0066] In the first step, 20 g of industrial alkali lignin was dissolved in 20 mL of methanol, and 20 mL of deionized water was added and stirred for 30 min. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain lignin nanoparticles;

[0067] In the second step, 15 g of lignin nanoparticles were dispersed in deionized water, 1 g of ferric chloride and 3 g of tannic acid were added and stirred for 60 min, and tannic acid / iron complexed lignin nanoparticles were obtained by centrifugation and freeze drying;

[0068] The third step is to take 14g of tannic acid / iron-complexed lignin nanoparticles, 20g of phenol, 8.5g of 37% formaldehyde solution, and 4.3g of barium hydroxide solution into a reaction container, and react at 75°C for 60min; then add 8.5g of 37% formaldehyde solution and 4.3g of sodium hydroxide solution, and heat at 85°C for 60min; then add 17g of 37% formaldehyde solution and 8.6g of barium hydroxide solution, raise the temperature to 95°C, keep warm for 90min, cool and discharge, and obtain a tannic acid-modified lignin phenolic resin antibacterial adhesive.

[0069] The bonding strength of the adhesive prepared in this example was tested using the same testing method as in Example 1, and the bonding strength was found to be 1.5 MPa.

[0070] Comparative Example 1

[0071] In the first step, 20 g of industrial alkali lignin was dissolved in 20 mL of methanol, and 60 mL of deionized water was added and stirred for 30 min. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain lignin nanoparticles;

[0072] In the second step, 12 g of lignin nanoparticles, 20 g of phenol, 8 g of 37% formaldehyde solution, and 3.2 g of potassium hydroxide solution were added to a reaction container and reacted at 75°C for 60 min; then 8 g of 37% formaldehyde solution and 3.2 g of sodium hydroxide solution were added and heated at 85°C for 60 min; then 16 g of 37% formaldehyde solution and 6.4 g of potassium hydroxide solution were added, the temperature was raised to 95°C, kept warm for 90 min, cooled and discharged, and a lignin phenolic resin adhesive was obtained.

[0073] The bonding strength of the adhesive prepared in this comparative example was tested using the same testing method as in Example 1, and the bonding strength was found to be 0.9 MPa.

[0074] Comparative Example 2

[0075] In the first step, 20 g of industrial alkali lignin was dissolved in 20 mL of methanol, and 20 mL of deionized water was added and stirred for 30 min. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain lignin nanoparticles;

[0076] In the second step, 14 g of lignin nanoparticles, 20 g of phenol, 8.5 g of 37% formaldehyde solution, and 4.3 g of barium hydroxide solution are added to a reaction container and reacted at 75° C. for 60 min; then 8.5 g of 37% formaldehyde solution and 4.3 g of sodium hydroxide solution are added and heated at 85° C. for 60 min; then 17 g of 37% formaldehyde solution and 8.6 g of barium hydroxide solution are added, the temperature is raised to 95° C., kept warm for 90 min, cooled and discharged, and a lignin phenolic resin adhesive is obtained.

[0077] The bonding strength of the adhesive prepared in this comparative example was tested using the same testing method as in Example 1, and the bonding strength was found to be 1.1 MPa.

[0078] Comparative Example 3

[0079] In the first step, 20 g of industrial alkali lignin was dissolved in 20 mL of methanol, and 20 mL of deionized water was added and stirred for 30 min. After the reaction was completed, the solution was dialyzed and freeze-dried to obtain lignin nanoparticles;

[0080] In the second step, 15 g of lignin nanoparticles were dispersed in deionized water, 1 g of ferric chloride and 3 g of tannic acid were added and stirred for 60 min, and tannic acid / iron complexed lignin nanoparticles were obtained by centrifugation and freeze drying;

[0081] The third step is to take 14g of tannic acid / iron-complexed lignin nanoparticles, 20g of phenol, 37g of 37% formaldehyde solution, and 17.2g of barium hydroxide solution and directly add them into a reaction container, react at 75°C for 60min, heat to 85°C for 60min, continue to raise the temperature to 95°C, keep warm for 90min, cool and discharge the material to obtain a tannic acid-modified lignin phenolic resin antibacterial adhesive.

[0082] The bonding strength of the adhesive prepared in this comparative example was tested using the same testing method as in Example 1, and the bonding strength was found to be 1.2 MPa.

[0083] With reference to the national standard GB / T 14732-2017, the solid content, pH, viscosity, free formaldehyde content and free phenol content of the adhesives prepared in the above embodiments and comparative examples were tested; at the same time, the antibacterial properties of the adhesives were tested by the inhibition zone method under 808nm near-infrared light irradiation, and the test results are shown in Tables 1 and 2.

[0084] Table 1 Main properties of adhesives

[0085]

[0086] Note: In Table 1, the lignin / phenol mass ratio refers to the percentage of tannic acid / iron-complexed lignin nanoparticles or lignin nanoparticles in the mass of phenol.

[0087] Table 2 Antibacterial properties of adhesives

[0088]

[0089]

[0090] As can be seen from Table 1, the adhesives prepared in the embodiments of the present invention and the comparative examples all meet the relevant parameters specified in the national standard GB / T14732-2017. Although the adhesives prepared in the comparative examples meet the provisions of the national standard GB / T 14732-2017 on viscosity, under the same preparation process, compared with Comparative Examples 1 and 2, due to the polyphenol structure of tannic acid, the reaction activity is enhanced, the viscosity of the adhesive in the embodiments increases, the content of free aldehyde and free phenol decreases, and the bonding strength is improved. In addition, under the same preparation process, compared with the one-time addition of formaldehyde and alkali solution in Comparative Example 3, the addition of formaldehyde and alkali solution in batches in each embodiment can effectively increase the viscosity of the adhesive, reduce the content of free aldehyde and free phenol, and improve the bonding strength.

[0091] It can be seen from Table 2 that under the same preparation process, compared with Comparative Examples 1 and 2, the adhesive in the embodiment shows a larger inhibition zone under near-infrared irradiation due to the presence of tannic acid / iron, indicating that it has better antibacterial effect; compared with Comparative Example 3 in which formaldehyde and alkali solution are added at one time, the adhesive prepared by adding formaldehyde and alkali solution in batches in each embodiment has improved antibacterial properties.

[0092] The above are only preferred specific embodiments of the present invention, but the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a tannic acid-modified lignin phenolic resin antibacterial adhesive, characterized in that: Alkali lignin is used as a raw material to obtain lignin nanoparticles through dialysis; the lignin nanoparticles are modified by tannic acid and ferric chloride to obtain tannic acid / iron complexed lignin nanoparticles; the tannic acid / iron complexed lignin nanoparticles are mixed with phenol, formaldehyde and alkali solution, and the tannic acid-modified lignin phenolic resin antibacterial adhesive is prepared through addition condensation reaction.

2. The method for preparing the tannic acid-modified lignin phenolic resin antibacterial adhesive according to claim 1, characterized in that: The following steps are involved: dissolving alkali lignin in an organic solvent, adding water and stirring to obtain a solution, dialyzing and freeze-drying the solution to obtain lignin nanoparticles; The lignin nanoparticles are dispersed in water, ferric chloride and tannic acid are added, and after the reaction is completed, the lignin nanoparticles are centrifuged and freeze-dried to obtain tannic acid / iron complexed lignin nanoparticles; The tannic acid / iron complexed lignin nanoparticles, phenol, part of the formaldehyde solution and part of the alkali solution are mixed, and reacted at 65-75° C. for 30-60 minutes; then part of the formaldehyde solution and part of the alkali solution are added, and heated at 75-85° C. for 30 minutes; then the remaining formaldehyde solution and the remaining alkali solution are added, the temperature is raised to 85-95° C., and the temperature is kept for 60-90 minutes, and the material is cooled and discharged to obtain the tannic acid modified lignin phenolic resin antibacterial adhesive.

3. The method for preparing the tannic acid-modified lignin phenolic resin antibacterial adhesive according to claim 2, characterized in that: The organic solvent is one of tetrahydrofuran, methanol and acetonitrile; and / or When preparing lignin nanoparticles, the volume ratio of the organic solvent to water is 1:(1-9).

4. The method for preparing the tannic acid-modified lignin phenolic resin antibacterial adhesive according to claim 1, characterized in that: The mass ratio of the lignin nanoparticles, ferric chloride and tannic acid is (10-20):(1-2):(2-4).

5. The method for preparing the tannic acid-modified lignin phenolic resin antibacterial adhesive according to claim 1, characterized in that: The mass of the tannic acid / iron complexed lignin nanoparticles is 30% to 70% of the mass of phenol.

6. The method for preparing the tannic acid-modified lignin phenolic resin antibacterial adhesive according to claim 2, characterized in that: The total amount of the formaldehyde solution added is 80% to 100% of the total mass of the phenol and tannic acid / iron complexed lignin nanoparticles, and the mass ratio of the formaldehyde solutions added successively is 1:1:2; and / or the formaldehyde solution is a formaldehyde solution with a mass concentration of 35% to 40%.

7. The method for preparing the tannic acid-modified lignin phenolic resin antibacterial adhesive according to claim 2, characterized in that: The total amount of alkali solution added is 30% to 50% of the total mass of the phenol and tannic acid / iron complexed lignin nanoparticles, and the mass ratio of the alkali solutions added successively is 1:2:2; and / or The mass concentration of the alkali solution is 40%.

8. The method for preparing the tannic acid modified lignin phenolic resin antibacterial adhesive according to claim 1, characterized in that: The viscosity of the tannic acid modified lignin phenolic resin antibacterial adhesive is 60-200 mPa·s.

9. A tannic acid modified lignin phenolic resin antibacterial adhesive, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the tannic acid modified lignin phenolic resin antibacterial adhesive according to claim 9 in the preparation of plywood.

Citation Information

Patent Citations

  • Lignin raw lacquer compound coating

    CN107955532A

  • Method for preparing lignin-based phenolic resin

    CN111484587A

Cited By

  • Bamboo board adhesive with high cohesiveness and preparation method of bamboo board adhesive

    CN119899612A

  • High-bonding-strength nano lignin-based formaldehyde-free adhesive as well as preparation method and application thereof

    CN121086756A

  • Injectable hydrogel for enhancing adhesion based on temperature-sensitive driving as well as preparation method and application of injectable hydrogel

    CN121754717A